Intervención urbana como estrategia para el aumento de espacio público efectivo en la ciudad de Neiva - Huila - Mario Andrés, Flores Vásquez (Universidad Antonio Nariño, 2022)
In this document, an analysis of the communes and their index of m2 of green areas, parks and squares per inhabitant in the municipality of Neiva-Huila. In the wake of This diagnosis shows that there is a high deficit of Effective Public Space in the city. For this reason, the need arises to choose a strategic point within the urban grid where presents more lack of public space per inhabitant and is the right place to generate an urban intervention. This responded to commune 6 since it is the largest sector of the city, with more inhabitants, with a greater area of ​​expansion and without urbanization of the municipality, where also evidenced the great lack of E.P.E per inhabitant, in addition to other problems that plague the community. This is why a proposal for an urban environmental project arose which consists of two phases, one is the road proposal that improves the connectivity of the commune 6 with the urban area, in the second instance, a linear park was proposed that contributes to the environment, recovering the main environmental setting of commune 6, which is the garden botanical Bertha de Ospina, which is currently abandoned, and the bodies of water surrounding areas, as well as the reduction of CO2 emissions and high temperatures due to the low biodiversity of the place. On the other hand, the generation of new open and pleasant spaces that are attractive, originating different activities for the general public, making it a landmark in the city.